Mutations of the Transcriptional Corepressor ZMYM2 Cause Syndromic Urinary Tract Malformations. - Connaughton, Dervla M; Dai, Rufeng; Owen, Danielle J; Marquez, Jonathan; Mann, Nina; GrAHm-Paquin, Adda L; Nakayama, Makiko; Coyaud, Etienne; Laurent, Estelle M N; St-Germain, Jonathan R; Blok, Lot Snijders; Vino, Arianna; et al. (Am J Hum Genet, 2020)
Congenital anomalies of the kidney and urinary tract (CAKUT) constitute one of the most frequent birth defects and represent the most common cause of chronic kidney disease in the first three decades of life. Despite the discovery of dozens of monogenic causes of CAKUT, most pathogenic pathways remain elusive. We performed whole-exome sequencing (WES) in 551 individuals with CAKUT and identified a heterozygous de novo stop-gain variant in ZMYM2 in two different families with CAKUT. Through collaboration, we identified in total 14 different heterozygous loss-of-function mutations in ZMYM2 in 15 unrelated families. Most mutations occurred de novo, indicating possible interference with reproductive function. Human disease features are replicated in X. tropicalis larvae with morpholino knockdowns, in which expression of truncated ZMYM2 proteins, based on individual mutations, failed to rescue renal and craniofacial defects. Moreover, heterozygous Zmym2-deficient mice recapitulated features of CAKUT with high penetrance. The ZMYM2 protein is a component of a transcriptional corepressor complex recently linked to the silencing of developmentally regulated endogenous retrovirus elements. Using protein-protein interaction assays, we show that ZMYM2 interacts with additional epigenetic silencing complexes, as well as confirming that it binds to FOXP1, a transcription factor that has also been linked to CAKUT. In summary, our findings establish that loss-of-function mutations of ZMYM2, and potentially that of other proteins in its interactome, as causes of human CAKUT, offering new routes for studying the pathogenesis of the disorder.
Keywords: Amphibian Proteins; Animals; Case-Control Studies; Child; Child, Preschool; DNA-Binding Proteins; Epigenesis, Genetic; Family; Female; Forkhead Transcription Factors; Heterozygote; Humans; Infant; Larva; Male; Mice; Mice, Knockout; Morpholinos; Mutation; Pedigree; Protein Binding; Repressor Proteins; Transcription Factors; Urinary Tract; Urogenital Abnormalities; Whole Exome Sequencing; Xenopus

Mutations in GDF11 and the extracellular antagonist, Follistatin, as a likely cause of Mendelian forms of orofacial clefting in humans. - Cox, Timothy C; Lidral, Andrew C; McCoy, Jason C; Liu, Huan; Cox, Liza L; Zhu, Ying; Anderson, Ryan D; Moreno Uribe, Lina M; Anand, Deepti; Deng, Mei; Richter, Chika T; Nidey, Nichole L; et al. (Hum Mutat, 2019)
Cleft lip with or without cleft palate (CL/P) is generally viewed as a complex trait with multiple genetic and environmental contributions. In 70% of cases, CL/P presents as an isolated feature and/or deemed nonsyndromic. In the remaining 30%, CL/P is associated with multisystem phenotypes or clinically recognizable syndromes, many with a monogenic basis. Here we report the identification, via exome sequencing, of likely pathogenic variants in two genes that encode interacting proteins previously only linked to orofacial clefting in mouse models. A variant in GDF11 (encoding growth differentiation factor 11), predicting a p.(Arg298Gln) substitution at the Furin protease cleavage site, was identified in one family that segregated with CL/P and both rib and vertebral hypersegmentation, mirroring that seen in Gdf11 knockout mice. In the second family in which CL/P was the only phenotype, a mutation in FST (encoding the GDF11 antagonist, Follistatin) was identified that is predicted to result in a p.(Cys56Tyr) substitution in the region that binds GDF11. Functional assays demonstrated a significant impact of the specific mutated amino acids on FST and GDF11 function and, together with embryonic expression data, provide strong evidence for the importance of GDF11 and Follistatin in the regulation of human orofacial development.

Redefining the Etiologic Landscape of Cerebellar Malformations. - Aldinger, Kimberly A; Timms, Andrew E; Thomson, Zachary; Mirzaa, Ghayda M; Bennett, James T; Rosenberg, Alexander B; Roco, Charles M; Hirano, Matthew; Abidi, Fatima; Haldipur, Parthiv; Cheng, Chi V; Collins, Sarah; et al. (Am J Hum Genet, 2019)
Cerebellar malformations are diverse congenital anomalies frequently associated with developmental disability. Although genetic and prenatal non-genetic causes have been described, no systematic analysis has been performed. Here, we present a large-exome sequencing study of Dandy-Walker malformation (DWM) and cerebellar hypoplasia (CBLH). We performed exome sequencing in 282 individuals from 100 families with DWM or CBLH, and we established a molecular diagnosis in 36 of 100 families, with a significantly higher yield for CBLH (51%) than for DWM (16%). The 41 variants impact 27 neurodevelopmental-disorder-associated genes, thus demonstrating that CBLH and DWM are often features of monogenic neurodevelopmental disorders. Though only seven monogenic causes (19%) were identified in more than one individual, neuroimaging review of 131 additional individuals confirmed cerebellar abnormalities in 23 of 27 genetic disorders (85%). Prenatal risk factors were frequently found among individuals without a genetic diagnosis (30 of 64 individuals [47%]). Single-cell RNA sequencing of prenatal human cerebellar tissue revealed gene enrichment in neuronal and vascular cell types; this suggests that defective vasculogenesis may disrupt cerebellar development. Further, de novo gain-of-function variants in PDGFRB, a tyrosine kinase receptor essential for vascular progenitor signaling, were associated with CBLH, and this discovery links genetic and non-genetic etiologies. Our results suggest that genetic defects impact specific cerebellar cell types and implicate abnormal vascular development as a mechanism for cerebellar malformations. We also confirmed a major contribution for non-genetic prenatal factors in individuals with cerebellar abnormalities, substantially influencing diagnostic evaluation and counseling regarding recurrence risk and prognosis.

Mutations in the Epithelial Cadherin-p120-Catenin Complex Cause Mendelian Non-Syndromic Cleft Lip with or without Cleft Palate. - Cox, Liza L; Cox, Timothy C; Moreno Uribe, Lina M; Zhu, Ying; Richter, Chika T; Nidey, Nichole; Standley, Jennifer M; Deng, Mei; Blue, Elizabeth; Chong, Jessica X; Yang, Yueqin; Carstens, Russ P; et al. (Am J Hum Genet, 2018)
Non-syndromic cleft lip with or without cleft palate (NS-CL/P) is one of the most common human birth defects and is generally considered a complex trait. Despite numerous loci identified by genome-wide association studies, the effect sizes of common variants are relatively small, with much of the presumed genetic contribution remaining elusive. We report exome-sequencing results in 209 people from 72 multi-affected families with pedigree structures consistent with autosomal-dominant inheritance and variable penetrance. Herein, pathogenic variants are described in four genes encoding components of the p120-catenin complex (CTNND1, PLEKHA7, PLEKHA5) and an epithelial splicing regulator (ESRP2), in addition to the known CL/P-associated gene, CDH1, which encodes E-cadherin. The findings were also validated in a second cohort of 497 people with NS-CL/P, comprising small families and singletons with pathogenic variants in these genes identified in 14% of multi-affected families and 2% of the replication cohort of smaller families. Enriched expression of each gene/protein in human and mouse embryonic oro-palatal epithelia, demonstration of functional impact of CTNND1 and ESRP2 variants, and recapitulation of the CL/P spectrum in Ctnnd1 knockout mice support a causative role in CL/P pathogenesis. These data show that primary defects in regulators of epithelial cell adhesion are the most significant contributors to NS-CL/P identified to date and that inherited and de novo single gene variants explain a substantial proportion of NS-CL/P.
Keywords: Alleles; Amino Acid Sequence; Animals; Biotinylation; Cadherins; Catenins; Cleft Lip; Cleft Palate; Epithelium; Female; Gene Deletion; Genetic Predisposition to Disease; Humans; Infant; Infant, Newborn; Male; Mice; Mutation; Palate; Pedigree; Syndrome; Whole Exome Sequencing